2021
DOI: 10.1101/2021.07.15.452525
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GPR39 Localization in Aging Human Brain and Correlation of Expression and Polymorphism with Vascular Cognitive Impairment

Abstract: INTRODUCTION: The pathogenesis of vascular cognitive impairment (VCI) is not fully understood. GPR39, an orphan G-protein coupled receptor, is implicated in neurological disorders but its role in VCI is unknown. METHODS: We performed GPR39 immunohistochemical analysis in postmortem brain samples from mild cognitive impairment (MCI) and control subjects. DNA was analyzed for GPR39 SNPs, and correlated with white matter hyperintensity (WMH) burden on premortem MRI. RESULTS: GPR39 is expressed in aged human dors… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…41 Peri-capillary pericytes, possibly through their GPR39 (G-protein-coupled receptor 39), respond to epoxyeicosatrienoates stimulation by increasing capillary caliber and, in turn augmenting nutritional microvascular blood flow. 19,42 In support of a role for dysfunctional pericytes in the impairment of capillary perfusion after ischemic stroke, we have recently reported that GPR39 gene deletion worsens microcirculatory response to experimental stroke in a sex-dependent manner. 43…”
Section: Discussionmentioning
confidence: 93%
“…41 Peri-capillary pericytes, possibly through their GPR39 (G-protein-coupled receptor 39), respond to epoxyeicosatrienoates stimulation by increasing capillary caliber and, in turn augmenting nutritional microvascular blood flow. 19,42 In support of a role for dysfunctional pericytes in the impairment of capillary perfusion after ischemic stroke, we have recently reported that GPR39 gene deletion worsens microcirculatory response to experimental stroke in a sex-dependent manner. 43…”
Section: Discussionmentioning
confidence: 93%